A Comparison of Solar Ultraviolet Radiation Exposure in Urban Canyons in Venice, Italy and Johannesburg, South Africa - (:unkn) unknown (My University, 2020)
Urban environments can have high-risk spaces that can provide excess personal sun exposure, such as urban or street canyons, and the spaces between buildings, among others. In these urban spaces, sun exposure can be high or low depending on several factors. Polysulphone film (PSF) was used to assess possible daily solar ultraviolet radiation (UVR) exposure in urban canyons in Venice, Italy and, for the first time in Africa, in Johannesburg, South Africa. The photodegradation of PSF upon solar exposure was monitored at a wavelength of 330 nm by ultraviolet-visible spectrophotometry, and the resultant change was converted to standard erythemal dose (SED) units (1 SED = 100 J m-2 ). Mean daily ambient solar UVR exposure measured for Venice and Johannesburg ranged between 20-28 SED and 33-43 SED, respectively. Canyon-located PSF exposures were lower in Venice (1-9 SED) than those in Johannesburg (9-39 SED), depending mainly on the sky view factor and orientation to the sun. There was large variation in solar UVR exposure levels in different urban canyons. These preliminary results should be bolstered with additional studies for a better understanding of excess personal exposure risk in urban areas, especially in Africa.
Keywords: African Research